Changes in brain response to urgency before and after treatment of urgency urinary incontinence with onabotulinumtoxin A. Issue 8 (29th July 2022) - Clarkson, Becky D.; Karim, Helmet T.; Chermansky, Christopher J.; Banihashemi, Layla; Tyagi, Shachi; Griffiths, Derek J.; Resnick, Neil M.
Abstract: Introduction: To better understand the role of the brain in urgency urinary incontinence (UUI), we used onabotulinumtoxin A (BoNTA) as a probe to evaluate changes in the brain's response to urgency in successful and unsuccessful treatment. Because BoNTA acts peripherally, brain changes observed should represent a reaction to changes in bladder function caused by BoNTA, or changes in the brain's compensatory mechanisms, rather than a direct effect of BoNTA on the brain. Methods: We recruited 20 women aged over 60 years with nonneurogenic UUI who were to undergo treatment with onabotulinum A toxin injected intravesically. We performed a baseline evaluation which included a 3‐day bladder diary and functional magnetic resonance imaging with an urgency provocation task; we repeated this evaluation 6 weeks posttreatment. We performed an analysis of variance on a priori selected regions of interest and post hoc voxel‐wise analysis on responders and nonresponders to treatment. Results: We found a significant interaction in the right insula [ F (1, 18) = 5.5, p = 0.031]; activity was different during urgency provocation in responders and non‐responders to therapy, before and after therapy. The supramarginal gyrus (SMG) and inferior frontal gyrus (IFG) also displayed significant interactions ( p < 0.005). Activity in the periaqueductal gray and prefrontal cortex was correlated with number of leakage episodes ( p < 0.05). Conclusion: The changes seen in the brain control mechanism after therapy likely reflect reduced bladder sensation caused by BoNTA's peripheral action. We ascribe the SMG and IFG changes to a coping mechanism for urgency which is reduced in those who respond well to treatment.